Implementation Of Balance Score Card As Measurement Of Employee Performance Of Muhammadiyah Mahakarya Aceh University - Bungsu, Agung Pangeran; Cahyono, Dwi; Sa'adah , Nur; Mursyidah4, Mursyidah; Muzakir, Fohan; Zikrullah , Zikrullah; Sari , Mena; Maisura, Maisura; Lestari, Evi (Universitas Muhammadiyah Jember, 2023)
The best tool for keeping an eye on an institution's performance is the Balanced Scorecard. similar to the workshop that was conducted at Muhammadiyah Mahakarya Aceh University, which was established in 2022 as a result of the union of four distinct establishments. Every organization has work that has to be done seriously: employee performance. The purpose of the balanced scorecard implementation workshop is to bring all staff members' goals together so they can support the university's ambitious performance and aspirations. This activity uses a Balanced Scorecard implementation technique, which is related to the goals, strategies, and targets specified through four (four) stages: program socialization, training, mentoring, and monitoring and evaluation. The ideas that each participant in this activity put forth to work together to further Muhammadiyah Mahakarya Aceh University inspired excitement